Developing nonuniform sampling strategies to improve sensitivity and resolution in 1, 1‐ADEQUATE experiments. (23rd March 2020) - Roginkin, Mark S.; Ndukwe, Ikenna E.; Craft, D. Levi; Williamson, R. Thomas; Reibarkh, Mikhail; Martin, Gary E.; Rovnyak, David
Abstract: Nonuniform sampling (NUS) strategies are developed for acquiring highly resolved 1, 1‐ADEQUATE spectra, in both conventional and homodecoupled (HD) variants with improved sensitivity. Specifically, the quantile‐directed and Poisson gap methods were critically compared for distributing the samples nonuniformly, and the quantile schedules were further optimized for weighting. Both maximum entropy and iterative soft thresholding spectral estimation algorithms were evaluated. All NUS approaches were robust when the degree of data reduction is moderate, on the order of a 50% reduction of sampling points. Further sampling reduction by NUS is facilitated by using weighted schedules designed by the quantile method, which also suppresses sampling noise well. Seed independence and the ability to specify the sample weighting in quantile scheduling are important in optimizing NUS for 1, 1‐ADEQUATE data acquisition. Using NUS yields an improvement in sensitivity, while also making longer evolution times accessible that would be difficult or impractical to attain by uniform sampling. Theoretical predictions for the sensitivity enhancements in these experiments are in the range of 5–20%; NUS is shown to disambiguate weak signals, reveal some n J CC correlations obscured by noise, and improve signal strength relative to uniform sampling in the same experimental time. This work presents sample schedule development for applying NUS to challenging experiments. The schedules developed here are made available for general use and should facilitate the broader utilization of ADEQUATE experiments (including 1, 1‐, 1, n‐, and HD‐ variants) for challenging structure elucidation problems. Abstract : Example connectivities in the sensitivity‐challenged 1, 1‐ADEQUATE experiment are illustrated for strychnine and demonstrate the need for using nonuniform sampling to sample long evolution times and improve sensitivity.